Blockade of the interleukin-2 receptor by anti-Tac antibody inhibits the generation of antigen-nonspecific suppressor T cells in vitro. - Oh-Ishi, T (1988)
The role of interleukin 2 (IL-2) in the activation of suppressor T cells was investigated by using the monoclonal antibody anti-Tac, which blocks the binding of IL-2 to the 55-kDa peptide of the high-affinity IL-2 receptor. Anti-Tac was added to an antigen-nonspecific suppressor system in which Con A-induced suppressor T cells were generated during a preculture period, and their effects on immunoglobulin production were assessed in second, indicator cultures containing pokeweed mitogen and peripheral blood mononuclear cells. Anti-Tac added during the preculture period inhibited Con A-induced suppressor T-cell generation. Cells activated by a short (2-day) preculture period to become effectors of suppression were primarily of the Tac-positive, T8 (CD8)-positive phenotype. Tac-positive, T8-negative T cells might also contribute to the suppressor activity. Our studies indicate that anti-Tac, by producing a functional blockade of human high-affinity IL-2 receptors, inhibits the generation of antigen-nonspecific suppressor T cells.